The Effect of Source of Organic Materials and Application Time on Growth and Yield of Beetroot (Beta vulgaris L.) in Dry Land - Suprihantono, Natalia Devinta; Suminarti, Nur Edy; Fajriani, Sisca (Plantropica: Journal of Agricultural Science, 2022)
Beetroot (Beta vulgarisÂ L.) is a horticultural plant that has many benefits that lie in tubers. Red beets are widely planted in highland areas with loose soil conditions. Currently, the expansion of land for food crops is experiencing problems due to limited productive land. The use of dry land as agricultural land has the main obstacles, namely low soil fertility, low organic matter content, and generally clay and dust-dominated soil. The application of organic matter needs to be added aiming to improve the physical properties of the soil, especially soil texture so that the soil becomes loose so that it does not hinder the tuber development process. The research was carried out from April 2020 to August 2020 at the Agro-Techno Park (ATP) Jatikerto garden. The study used a split-plot design with organic material sources as the main plot, namely B1: goat manure, B2: Azolla compost, B3: UB compost, and the time of application as subplots, namely T1: simultaneously planting, T2: 1 month before planting, and T3 : 2 months before planting. Observational data were analyzed using analysis of variance (Test F), if there was an influence between treatments, further tests were carried out using the Honest Significant Difference (BNJ) test. The results showed that the use of UB compost was better applied 1 month before planting because it produced high tuber weight per harvest plot and was more profitable. Based on the results of farming analysis, the use of UB compost with an application time of 1 month before planting is feasible to cultivate with an R/C reaching 3.67.